Arduino Mega Based System Design for Sequence and Phase Difference Detection of Three-Phase Systems - Nrartha, I Made Ari; Saputra, Ahmad Sandi Yayan; Supriono, Supriono; Hasibuan, Arnawan; Sayuti, M; Al-Ani, Waleed Khalid Ahmed (Journal of Renewable Energy, Electrical, and Computer Engineering, 2022)
In a three-phase system, the difference in the angle between the phases and the phase sequence of the system is very important to ensure the system functions normally and does not cause damage to the three-phase equipment connected to the system. Trigonometric formulas in multiphase systems are used to obtain the angle difference between the phases and the sequence of phases in the system. The trigonometric formula was tested in a simulation using MATLAB software, then applied to an Arduino Mega-based system. In the simulation, the data are two voltages vs. time with a certain phase angle difference, then using the trigonometric formula in the MATLAB program, the data is recovered from the phase angle difference and the direction of rotation of the two voltages. Based on the valid MATLAB simulation test results, the program algorithm is embedded in an Arduino Mega-based system equipped with 2 voltage sensors and a 2.4-inch TFT LCD. The Arduino Mega-based system has succeeded in detecting and visualizing in the form of a graph the angle difference between the phases and the direction of rotation of the three-phase system.